2017
DOI: 10.21873/anticanres.11795
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-Catenin Signaling Inhibitor IC-2 Suppresses Sphere Formation and Sensitizes Colorectal Cancer Cells to 5-Fluorouracil

Abstract: Abstract. Background Colorectal cancer (CRC) is one of the most common cancer types in the world and carries the second highest mortality rate (1). Although initial events in CRC are relatively well studied and treatment for early-stage disease has significantly improved over the past decades, the mechanisms of metastasis and relapse, which are the main causes of death, remain poorly characterized (2). Currently, no effective therapy is available for advanced or metastatic disease and the survival rate at 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…CD44 being a Wnt/β-catenin target gene, along with other studies indicating the link between Wnt/β-catenin signaling pathway, CSC and chemoresistance ( 35 , 36 ), we determined the expression of β-catenin. In HCT 116 cells, OX treatment was found to inhibit the accumulation of β-catenin ( Figures 6E,F ) while in HT 29 cells a significant accumulation of β-catenin was observed with OX treatment ( Figures 6G,H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD44 being a Wnt/β-catenin target gene, along with other studies indicating the link between Wnt/β-catenin signaling pathway, CSC and chemoresistance ( 35 , 36 ), we determined the expression of β-catenin. In HCT 116 cells, OX treatment was found to inhibit the accumulation of β-catenin ( Figures 6E,F ) while in HT 29 cells a significant accumulation of β-catenin was observed with OX treatment ( Figures 6G,H ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Urushibara et al ( 35 ) tried to inhibit the expression of CSC proteins using a Wnt/β-catenin signaling inhibitor “IC-2” and found enhanced cytotoxicity to the drug 5-FU (fluorouracil) by colon cancer cells. Another study by Chen et al ( 36 ) has shown that suppression of Axin2 (a negative feedback regulator of Wnt/β-catenin signaling) by micro RNA: miR-103/107 enhanced chemoresistance of colon cancer cells via inducing stemness.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , Western blot and immunohistochemistry assay showed that expression of β-catenin protein was decreased mice treated with IC-2 (5 mg/kg) and the tumor volume was also reduced, suggesting that IC-2 inhibits bladder cancer in vivo . In CRC cells, IC-2 reduced Wnt/β-catenin transcriptional activity and decreased the expression levels of cancer stem cell marker proteins [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diallyl trisulfide inhibits CRC stem cells by promoting the expression of GSK-3β and inhibiting the expression of β-catenin and CRC stem cell markers in CRC stem cells ( 49 ). IC-2, a derivative of Wnt/β-catenin signaling inhibitor ICG-001, inhibits the expression of CRC stem cell marker proteins, as well as the sphere formation activity of CRC cells ( 102 ). ICG-001 promotes cell differentiation, suppresses cell proliferation, and induces apoptosis via binding to CREB-binding protein in CRC cells ( 103 , 104 ), suggesting that IC-2 may also bind to this protein to suppress the sphere formation of CRC cells via inhibition of the expression of CRC stem cell markers.…”
Section: Therapeutic Strategies Targeting Wnt/β-catenin Signaling For Crcmentioning
confidence: 99%